PAOLO MANTEGAZZA: OLTRE LA SCIENZA (Istituto Lombardo - Accademia di Scienze e Lettere • Incontri di Studio, 2018)
Even a scientist is a man, and to reduce him down to what he has attained in research labs is not fair. A man’s existence is much richer, composed of relationships and feelings and these relationships have an effect even on the rationality of which the scientific methodology is based. For this reason, after many have described the scientist Mantegazza, I wanted to illustrate his personal characteristics. And it is so that a portrait of a great man transpired, an example not to be forgotten, a great professor of pharmacology.